The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2001
DOI: 10.1099/00221287-147-5-1095
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genetic characterization of Listeria monocytogenes isolates from human and animal listeriosis cases

Abstract: Listeria monocytogenes isolates from human sporadic and epidemic cases (n l 119) and from animal cases (n l 76) were characterized by automated ribotyping and PCR-restriction fragment length polymorphism (PCR-RFLP) typing of the virulence genes actA and hly. This combination of typing methods differentiated 39 distinctive strains, each reflecting a unique combination of ribotypes, hly and actA alleles. Simpson's index of discrimination indicated a high discriminatory ability of ribotyping for both animal (0867… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
169
0
9

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 211 publications
(196 citation statements)
references
References 37 publications
18
169
0
9
Order By: Relevance
“…Isolates in lineage III are known to be more prevalent in animals with clinical Listeriosis (Jeffers et al, 2001). What was also significant was that isolates belonging to division II were not detected; no isolates were positive for PCR using D2 specific primers.…”
Section: Discussionmentioning
confidence: 95%
“…Isolates in lineage III are known to be more prevalent in animals with clinical Listeriosis (Jeffers et al, 2001). What was also significant was that isolates belonging to division II were not detected; no isolates were positive for PCR using D2 specific primers.…”
Section: Discussionmentioning
confidence: 95%
“…Two of these lineages (I and II) cause predominantly human infections, whereas lineages III and IV have never been involved in human disease, being responsible of clinical listeriosis in animals (Jeffers et al, 2001;Nightingale, 2010). The explanation of this finding is unknown, since both lineages share most of known virulence factors.…”
Section: Ecology Of Listeria Monocytogenes and Molecular Subtyping Mementioning
confidence: 99%
“…In other words, although food is a major source of human infection, not all strains that contaminate food possess a similar virulence potential to cause invasive infection in humans. Analysis of domestic animal and farm environmental isolates revealed that some strains associated with human infection circulate in the agricultural complexes [20]. Although the role of the wild nature as an original source of listerial infection was suggested, the information about clone distribution among L. monocytogenes disseminated in natural ecosystems and their phylogenetic relationships with epidemiologically important clones is scarce [13; 19; 54].…”
Section: Introductionmentioning
confidence: 99%